Effects of BN/GO on the recyclable, healable and thermal conductivity properties of ENR/PLA thermoplastic vulcanizates. (January 2022) - Jia, Chunhui; Zhang, Ping; Seraji, Seyed Mohsen; Xie, Ruishi; Chen, Lin; Liu, Dong; Xiong, Ying; Chen, Hao; Fu, Yingke; Xu, Hailun; Song, Pingan
Highlights: Amino-functionalized BN was successfully fabricated by ball milling. Covalent bonded BN/GO as thermal conductivity filler to promote the dispersion of the BN in matrix ENR/PLA. The obtained BN/GO/ENR/PLA composites exhibited good heat management capability. The obtained BN/GO/ENR/PLA composites exhibited excellent recoverable and self-healing efficiency. Abstract: Owing to the increasing heat dissipation problem of advanced modern electronic devices, polymer composites with high thermal conductivity have received extensive attention in recent years. Here, the high thermally conductive composites are prepared with a polymer matrix of epoxidized natural rubber (ENR)/polylactic acid (PLA) blend and a nano-additive hybrid system of boron nitride (BN)/graphene oxide (GO). To promote the dispersion of filler in ENR/PLA matrix, BN was covalently bonded with GO. When the contents of BN/GO into ENR/PLA composites was 14 wt%, a massive 240% enhancement of thermal conductivity, recoverable performance (85% of tensile strength after post forming compared to that of original composites), self-healing effect (86% of tensile strength after self-healing compared to that of original composites, respectively. The proposed composites system (BN/GO/ENR/PLA) will provide valuable insights for the application of polymers in electronic devices.